PEMETAAN WILAYAH POTENSIAL TERNAK RUMINANSIA MENGGUNAKAN ANALISIS LQ DAN ArcGIS KABUPATEN MANGGARAI TAHUN 2024: MAPPING OF RUMINANT LIVESTOCK POTENTIAL AREAS USING LQ and ArcGIS ANALYSIS OF MANGGARAI REGENCY IN 2024 - Dalle, Nautus Stivano; Sikone, Hilarius Yosef; Tukan, Hendrikus Demon; Sumarmono, Juni; Nurdin; Sijung, Maria Dortiana (Universitas Boyolali, 2025)
This study aims to map the potential area of ruminant livestock farming in Manggarai Regency based on the results of the Location Quontient (LQ) calculation. This study uses LQ calculations and then interprets them on maps using ArcGIS applications. Livestock population data in Manggarai Regency was obtained from data from the Manggarai Regency Livestock Service in 2024 based on 12 districts in Manggarai Regency. Based on the results of the calculation of the sub-districts of Satar Mese, Satar Mese Barat, Satar Mese Utara, Ruteng, West Cibal, Reok and West Reok, the results of LQ>1 for cattle commodities were obtained. Meanwhile, in the Satar Mese, North Satar Mese, West Mese Satar, North Rahong, West Cibal and Cibal sub-districts also received LQ>1 results for buffalo livestock commodities. And for the areas of West Mese Star, Cibal, West Cibal, West Reok and North Rahong, the results of LQ>1 for goat livestock were obtained. The conclusion of this study is that local governments must support efforts to increase livestock production based on the results of the LQ<1 calculation such as Langke Rembong, Wae Ri'i and Lelak sub-districts.